Contextual interference and level of skill in the learning of volleyball serve - Nhamussua, Domingos Manuel; Prista, António; Basso, Luciano; Tani, Go (Brazilian journal of physical education and sport, 2012)
The purpose of this study was to investigate the effect of contextual interference on acquiring the volleyball serve in adolescents with different skill levels, considering then immediate and delayed transfer tests. Participants were 56 schoolgirls separated in four practice groups: random practice with higher level skill subjects (GAS), blocked practice with higher level skill subjects (GBS), random practice with lower level skill subjects (GAI) and blocked practice with lower level skill subjects (GBI). The acquisition task consisted in performing underhand and overhead services directed at two targets affixed to the ground. The results showed no effect of contextual interference on the lower level skill subjects. However when comparing the types of practice between the higher level skill subjects, the effect was observed in the immediate transfer test. The absence of significant differences between groups in the delayed transfer test suggest that the contextual interference effect may be temporary.